Stories of practice : preservice teachers' perceptions of information and communications technology - Hart, Stephen Robert (My University, 2009)
This thesis investigates the perceptions of information and communications technology (ICT) held by four preservice teachers as they engage in their first field-based practicum. Perceptions result from interactions between the participants’ educational beliefs about ICT and their field-based experiences with it. The research was conducted using qualitative research techniques derived from narrative and collective case study methodology. Questionnaires completed prior to the practicum, journal entries created during the practicum, and open-ended interviews conducted immediately after the practicum, provide contextualized biographical and narrative data. Within-case analysis of the data resulted in the production of four individual case vignettes that reveal the significant experiences and prevailing beliefs of each participant. The narrative accounts render the participants’ perceptions available and comprehensible to the reader. A cross-case analysis explores themes that hold across the four cases. It indicates that preservice teachers conceive ICT in terms of its perceived educational value and their perceived capacity to use it. These findings, it is suggested, can enlighten initial teacher education programs by informing theory, by informing practice, and by informing future research.
Keywords: Student teachers.